EngageHealth: a mobile device application designed to deliver stroke rehabilitation exercises using asynchronous video recordings - Song, Andrew J.; Lugo, Leonel; Muccini, Julie; Mlynash, Michael; Lansberg, Maarten G. (Frontiers in Stroke, 2024)
Background Stroke survivors who receive more rehabilitation therapy achieve better functional outcomes. The amount of rehabilitation that patients receive is, however, limited due to constraints of the healthcare system. Objective To assess whether EngageHealth, a mobile device application designed to deliver stroke rehabilitation exercises using asynchronous video recordings, increases the amount of outpatient rehabilitation in stroke patients and improves their upper extremity function and quality of life. Design Prospective single-arm study consisting of a 2-week pre-intervention phase without EngageHealth followed by a 4-week intervention period with EngageHealth. Setting Ambulatory care. Participants Twenty-four stroke patients with upper extremity impairment were recruited at the Stanford Stroke Center outpatient clinic. Interventions Participants were instructed to use the EngageHealth application daily. Main outcome measures Adherence, user experience, and change in the upper extremity Fugl-Meyer (UE-FM), Quality of Life in Neurological Disorders (Neuro-QoL), and Stroke Impact Scale (SIS). Results Of 23 participants, five (22%) used the application for 17 days, six (26%) used the application for 9–16 days, and 12 (52%) used it < 9 days. Sixty-three percent of participants would recommend the application to other stroke survivors, with fifty percent indicating they would continue using the application, if available. During the pre-intervention phase, there were no changes in hand function. During the intervention period, participants improved by 4 points on the UE-FM (P < 0.01), and 15 points in the hand-function domain of SIS (P = 0.03). Videos of participants' exercises were successfully recorded, allowing the clinician to review videos of the participants' completed tasks asynchronously. In-depth interviews revealed that participants viewed the EngageHealth application favorably, and that their perceived usefulness of the exercises affected their motivation. Conclusions Use of the EngageHealth application in the home environment may improve upper extremity function in subacute/chronic stroke patients. Additional support strategies should be implemented in future studies to improve adherence. These findings from a prospective single-arm study, support the design of a randomized controlled trial to determine the efficacy of long-term use of the EngageHealth application.